Building Sustainable Employee Engagement in the EPC Industry: The Role of Career Development, Organizational Justice, and Perceived Organizational Support - Hendrawan, Tommy Budi; Iqbal, M. Ali (Indonesian Journal of Business Analytics, 2025)
This study examines the effects of career development and organizational justice on sustainable employee engagement, with perceived organizational support (POS) as a mediating variable. Using Social Exchange Theory, the research tested a structural model based on data from 149 permanent employees of PT Enviromate Technology International (ETI), collected via questionnaire during 2025. Data were analyzed using SmartPLS. Results show that career development directly and indirectly enhances sustainable engagement via POS, while organizational justice only exerts an indirect effect through POS. The findings highlight the strategic importance of POS in fostering long-term engagement and offer theoretical insights into HR practices within the EPC sector.